2018
DOI: 10.4049/immunohorizons.1800008
|View full text |Cite
|
Sign up to set email alerts
|

A Major Population of Functional KLRG1– ILC2s in Female Lungs Contributes to a Sex Bias in ILC2 Numbers

Abstract: Humans show significant sex differences in the incidence and severity of respiratory diseases, including asthma and virus infection. Sex hormones contribute to the female sex bias in type 2 inflammation associated with respiratory diseases, consistent with recent reports that female lungs harbor greater numbers of GATA-3–dependent group 2 innate lymphoid cells (ILC2s). In this study, we determined whether sex hormone levels govern sex differences in the numbers, phenotype, and function of ILC2s in the murine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 68 publications
11
85
1
Order By: Relevance
“…ILC2 progenitor cells (ILC2Ps) in the bone morrow express androgen receptor (AR) mRNA although estrogen receptor ( Esr1 and Esr2 ) mRNA are undetectable . In male mice, the number of ILC2 progenitor cells is decreased, whereas the frequency of PLZF + ILC progenitor cells is increased, which suggests that endogenous androgen inhibits the differentiation of ILC2s. Furthermore, CD25 expression is decreased in male ILC2Ps and mature ILC2s.…”
Section: Hormones (Androgen and Estrogen)mentioning
confidence: 99%
“…ILC2 progenitor cells (ILC2Ps) in the bone morrow express androgen receptor (AR) mRNA although estrogen receptor ( Esr1 and Esr2 ) mRNA are undetectable . In male mice, the number of ILC2 progenitor cells is decreased, whereas the frequency of PLZF + ILC progenitor cells is increased, which suggests that endogenous androgen inhibits the differentiation of ILC2s. Furthermore, CD25 expression is decreased in male ILC2Ps and mature ILC2s.…”
Section: Hormones (Androgen and Estrogen)mentioning
confidence: 99%
“…There is also a growing body of evidence suggesting ILC2s exhibit sexual dimorphism. Depending on the tissue, ILC2s express androgen and estrogen receptors and this signaling can alter their activity [67][68][69][70][71] (Figure 1). Androgens suppress lung ILC2s and appear to inhibit differentiation of ILC2 progenitors from the bone marrow, whereas estrogen has the opposite effect on uterine ILC2s [67][68][69][70][71].…”
Section: Diversity Of Ilc2smentioning
confidence: 99%
“…Depending on the tissue, ILC2s express androgen and estrogen receptors and this signaling can alter their activity [67][68][69][70][71] (Figure 1). Androgens suppress lung ILC2s and appear to inhibit differentiation of ILC2 progenitors from the bone marrow, whereas estrogen has the opposite effect on uterine ILC2s [67][68][69][70][71]. Interestingly, multiple reports have found that male mice have fewer tissue resident ILC2s within multiple organs, though it is not yet known whether this is the case in humans [67,69,71].…”
Section: Diversity Of Ilc2smentioning
confidence: 99%
See 1 more Smart Citation
“…Female ILC2s are more responsive upon ex vivo cytokine stimulation compared to male, due to inhibitory effects of androgen signaling (Cephus et al., ; Laffont et al., ; Warren et al., ). It is also known that the number of ILC2s that are negative for KLRG1 in females increases with age and contributes to the higher numbers of ILC2s in female lungs (Kadel et al., ). This should be taken into consideration as well as the tissue‐dependent effect of sex hormones (Bartemes et al., ).…”
Section: Commentarymentioning
confidence: 99%